2020
DOI: 10.1123/ijspp.2019-0715
|View full text |Cite
|
Sign up to set email alerts
|

Strength-Training Periodization: No Effect on Swimming Performance in Well-Trained Adolescent Swimmers

Abstract: Purpose: To assess the effects of periodized versus nonperiodized dry-land strength training (DLST) on indices of swimming performance in well-trained adolescent swimmers. Methods: Sixteen athletes (10 boys and 6 girls; age 14.9 [1.1] y) performed similar endurance training for 16 weeks (29.1 [7.5] km·wk−1). During weeks 1 to 7, all athletes additionally performed 2 or 3 times weekly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Tanaka et al [ 47 ] was the only study in this subgroup of training interventions that reported no positive effects after the training intervention, but Tanaka and colleagues were not alone in the lack of positive gains in swimming performance. Sawdon-Bea and Benson [ 45 ] and Schumann et al [ 42 ] did not find significant changes in swimming performance. Junior et al [ 48 ] found significant improvement in a separate 25 m all-out sprint but not in the 50 m front crawl performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tanaka et al [ 47 ] was the only study in this subgroup of training interventions that reported no positive effects after the training intervention, but Tanaka and colleagues were not alone in the lack of positive gains in swimming performance. Sawdon-Bea and Benson [ 45 ] and Schumann et al [ 42 ] did not find significant changes in swimming performance. Junior et al [ 48 ] found significant improvement in a separate 25 m all-out sprint but not in the 50 m front crawl performance.…”
Section: Resultsmentioning
confidence: 99%
“…From the 27 identified articles, 10 examined specific in-water resistance training with resistance bands [ 29 32 ], hand paddles [ 33 ], drag suit or parachute training [ 34 , 35 ], leg kicking training [ 36 ], arms-only training [ 37 ] and training with a specialized fixed push-off point (POP) device [ 38 ]. Four studies investigated swim-like specific dry-land resistance training [ 21 , 39 – 41 ], and 11 studies focused on non-specific dry-land strength training [ 8 , 9 , 42 – 51 ]. Junior et al [ 48 ] and Girold et al [ 12 ] had two intervention groups and one control group, whereas one intervention group performed specific in-water resistance training and the other group performed non-specific dry-land strength training.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high demand for leg muscles during push off from the wall [ 11 , 33 ] and repeated breath holding during the underwater phase [ 32 ] may have resulted in a fatigue effect during short-course races. However, swimmers accelerate beyond free-swimming speed with the push-off after the turn and swimming performance should basically benefit from the larger resistance provided by the pool wall assuming an adequate conditioning for leg muscles [ 36 ]. Therefore, swimmers may have applied a more careful pacing strategy and more energy conserving turns due to higher number of turns available in short-course races.…”
Section: Discussionmentioning
confidence: 99%
“…Moderator variables include training principles such as intensity, frequency, type, volume and periodization and so on [15]. Of those, RT programming has assumed a special importance and are usually more effective than constant (nonvaried) RT programs [14,[16][17][18][19], even if this trend is not universal [20,21]. Linear and undulating programming are two common methods of engaging in RT [18,22].…”
Section: Introductionmentioning
confidence: 99%